Proprium hominis : the person and his moral life in the biblical commentaries of Thomas Aquinas (Sapientia, 2019)
The paper starts with the sentence from the sermo Homo quidam: «What is proper to man? Being mild in nature (”¦) So, because of our similarity and intimacy with God and his property, anyone ought to be uncorrupted, devoted to God and kind to his neighbor» and I will try to analyze the virtues of mansuetudo and benignitas in biblical commentary of Aquinas (but also ethical consequences of Deo devotus). There will be a place for some general remarks about Aquinas virtue ethic.
Keywords: Thomas Aquinas; Meekness; Biblical Thomism; Passions